2014
DOI: 10.1111/cote.12100
|View full text |Cite
|
Sign up to set email alerts
|

A general metric for the magnitude of observer metamerism

Abstract: Observer metamerism is defined as a property of a pair of spectrally different stimuli having the same colour sensation for an individual (reference) observer. Frequently, samples in this pair no longer match if the observer is changed. In this article, a linear approximation formula is developed that predicts a metameric effect caused by small changes in the observer's colour‐matching functions. This approximation formula enables a general metric of observer metamerism, the observer metamerism potential, to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…To avoid the influence of capture conditions, DigiEye system 17 was utilized for image capture. As shown in Figure 3(a), this system is equipped with a Nikon D7000 camera, special pick-up head and standard illumination D65, 18 which has the advantages of small color difference and stable capture condition. After capture, the image was cropped in the size of 1000 pixels  1000 pixels to reduce the parts of edge burr and platen, as shown in Figure 3(b).…”
Section: Image Capture and Pre-processingmentioning
confidence: 99%
“…To avoid the influence of capture conditions, DigiEye system 17 was utilized for image capture. As shown in Figure 3(a), this system is equipped with a Nikon D7000 camera, special pick-up head and standard illumination D65, 18 which has the advantages of small color difference and stable capture condition. After capture, the image was cropped in the size of 1000 pixels  1000 pixels to reduce the parts of edge burr and platen, as shown in Figure 3(b).…”
Section: Image Capture and Pre-processingmentioning
confidence: 99%
“…For example, Sluban et al reported a general metric for the magnitude of observer metamerism. 6 In another study, Peyvandi et al reported the illuminant metamerism potentiality of metameric pairs. 8…”
Section: Introductionmentioning
confidence: 98%
“…The color of an object is a sensation rather than a particular property. 6 Metamerism is the name given to the phenomenon in which a pair of color stimuli, differing in spectral distribution, match in color under certain conditions, and not in others. 7 The degree of deviation from matching is known as the degree of metamerism and can be expressed by the metamerism index.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above method, Xu et al 39 introduced a mixture of weights such that the selected training samples were about half the size of those in the method used by Cao et al The test yielded that using 100 training samples was sufficient. It ends up using less processing time than the method used by Cao et al In addition to this, Sluban et al 40 found that different observers cause different homochromatic heterospectral effects, so they proposed a linear approximation formula to solve this problem.…”
Section: Introductionmentioning
confidence: 99%